Clinical Features Associated with Mutations in the Chromosome 1 Open-Angle Glaucoma Gene (GLC1A) - Alward, Wallace L.M; Fingert, John H; Coote, Michael A; Johnson, A. Tim; Lerner, S. Fabian; Junqua, Denise; Durcan, Fiona J; McCartney, Paul J; Mackey, David A; Sheffield, Val C; Stone, Edwin M (The New England journal of medicine, 1998)
Glaucoma is a disorder of the optic nerves that is characterized by cupping of the optic-nerve head and loss of peripheral vision. Occasionally, there is also loss of central vision. Intraocular pressure is elevated in the majority of cases and is thought to contribute to the optic-nerve damage. The disease is insidious, and affected patients frequently have no symptoms. In over 90 percent of patients with glaucoma, the trabecular meshwork appears to be completely normal on clinical examination, and as a result, such patients are said to have open-angle glaucoma. The age at onset of open-angle glaucoma ranges from less . . .